Probing Transient Photoinduced Charge Transfer in Prussian Blue Analogues with Time‐Resolved XANES and Optical Spectroscopy. Issue 3 (20th July 2017) - Zerdane, Serhane; Cammarata, Marco; Balducci, Lodovico; Bertoni, Roman; Catala, Laure; Mazerat, Sandra; Mallah, Talal; Pedersen, Martin N.; Wulff, Michael; Nakagawa, Kosuke; Tokoro, Hiroko; Ohkoshi, Shin‐ichi; et al.
Abstract : We studied the transient electron‐transfer process in CsCoFe and RbMnFe Prussian Blue analogues by time‐resolved X‐ray absorption near‐edge structure (XANES) and by time‐resolved optical spectroscopy. We performed time‐resolved studies on CsCoFe nanocrystals dispersed in solution. The XANES results obtained at room temperature clearly evidence Co III (low spin)Fe II →Co II (high spin)Fe III electron transfer between the metal centers through opposite spectral shifts at the Fe and Co edges. We also studied the Mn III (low spin)Fe II →Mn II (high spin)Fe III process in an RbMnFe powder sample at thermal equilibrium and under laser excitation. Optical spectroscopy revealed that the process occurs on the picosecond timescale, as already reported by Raman spectroscopy, and that the lifetime of the photoinduced charge‐transfer states is in the 1–10 µs range, depending on the sample and temperature. Abstract : We studied the transient electron‐transfer process induced by a femtosecond laser pulse in nanocrystals of CsCoFe and RbMnFe Prussian Blue analogues by time‐resolved X‐ray absorption near‐edge structure and time‐resolved optical spectroscopy. The results clearly evidence ultrafast Co III (low spin)Fe II →Co II (high spin)Fe III and Mn III (low spin)Fe II →Mn II (high spin)Fe III electron‐transfer processes.